Imago Dei: We are but dust and shadow - Rabie-Boshoff, Annelien C. (HTS teologiese studies, 2021)
This article is about the imago Dei, proceeding from an ecotheological perspective. Both the ‘image of God’ and the ‘likeness of God’ are examined based on the understanding that God is a relational God. It approaches the question of the imago Dei in terms of God’s incorporeal nature, and what it is that human beings have in common with God apart from the human being’s capacity for personal and interpersonal relationships. It addresses the question of the imago Dei in terms of God’s spiritual nature and the human being’s ‘earthly’ nature by utilising the metaphor of ‘shadow’. This metaphor was investigated in terms of its meaning in Hebrew (tselem), and Genesis 2:7–8 where the creation of the human being is described in terms of God breathing the breath of life into the human being. A distinction has been drawn between the ‘image of God’ and the ‘likeness of God’, with the ‘likeness of God’ (demuth) that was investigated in the context of Exodus 31:1–5, and the various spiritual gifts conferred to Bezalel by the Spirit of God. Based on this investigation the article posits that the imago Dei as the Shadow of God (life) has been bestowed on all living creatures and not only human beings.Contribution: The suggestion that the imago Dei as the Shadow of God is present in all of the creation urges us to seek further and look deeper into the issue of imago Dei in the sense that such an understanding pointedly has far-reaching implications for the current understanding of the place of human beings in creation. In consideration of this, it bears on our understanding of the meaning of life within the bigger picture of creation and how we respond to the living environment with which we share life.